Fiscal policy responses for sustainable post-COVID-19 recovery: Taiwan's experience. Issue 2 (9th November 2021) - Kuo, Yu-Ying
Abstract : Purpose: This study examined Taiwan's fiscal policy responses for sustainable post-COVID-19 recovery. The costs and benefits, aligned with Sustainable Development Goals (SDGs), of fiscal policy responses were identified and valued. Although it may be too early to conclude whether the benefits outweigh the costs, the performance and outcome of fiscal measures were evaluated. Design/methodology/approach: The study relied on secondary data, including governmental official data, legislative reviews, audit reports and public opinion polls to understand objective and subjective benefits and costs in economic, social and environmental dimensions. However, while the costs were measured in monetary terms, some of the benefits (i.e. satisfaction) could not be monetized; therefore, this study focused on identifying and valuing benefits from fiscal measures but set aside the issues of monetizing and discounting. Findings: With respect to the costs, a special budget of NT840 billion was approved, of which 66.83% was allocated for economic development, 33.12% for social welfare and 0.05% for environmental protection. In terms of the benefits, the economic growth rate was forecasted to be 5.88% in 2021 and 3.69% in 2022, while the average economic growth rate was 2.77% during the period from 2012 to 2019. Social equity was emphasized as various and customized bailout packages were provided to impacted individuals and industries. Moreover, most citizens were confident in the government's efforts to combat the pandemic and stimulate recovery in Taiwan. Originality/value: This paper comprehensively details Taiwan's experience of fiscal policy responses for sustainable post-COVID-19 recovery. The cost-benefit approach was conceptually adopted. Bearing the value of "build back better" and "rebuild better, " the benefits of fiscal measures are promising, although there are indebted costs of the special budget.